Implementasi Range of Motion untuk Meningkatkan Kekuatan Otot Ekstremitas Pasien Stroke dengan Hambatan Mobilitas Fisik - Chris Dwi Anto; Prasanti Adriani; Yusmiranti; Dwi Novitasari (Yayasan Inspirasi El Burhani, 2022)
Introduction: Non-hemorrhagic stroke is a stroke caused by the existence of blockage that occurs as a result of a thrombus in vessels, blood-brain, or clot blood caused by the embolic process. A stroke causes several complications such as cerebral edema, increased intracranial pressure, seizures, hemorrhagic transformation, pneumonia, urinary tract infections, venous thrombosis, and impaired daily activities. Nurses must provide nursing care to overcome barriers to the physical mobility of non-hemorrhagic stroke patients. Objective: This activity was conducted to describe the implementation of nursing practice Range of Motion on Mrs. R with a non-hemorrhagic stroke who had impaired physical mobility. Method: Research this use method studies case with design writing descriptive. The approach used that is with approach implementation of nursing covers measuring a patient's vital signs, measuring the strength of muscle extremities patient, give practice Range of Motion, and giving therapy pharmacological. Result: After being given the Range of Motion exercise to Mrs. R, which was carried out for three days showed that the patient's muscle strength had increased, while the patient's impaired physical mobility had not been overcome. Conclusion: It is necessary to do Range of Motion at least twice a day with a time of 10 to 15 minutes to maximize the increase in extremity muscle strength in non-hemorrhagic stroke patients.